The Relationship Of Stress Level With Menstrual Cycle Disorders In SMK Health Nafsiah Stabat Year 2022 - Emma Frida Manurung (Science Midwifery, 2022)
High and continuous stress can endanger the health of adolescents, where adolescents are the forerunners of the nation's successors. The future of the nation is in their hands. Adolescent girls as teenagers besides being the nation's successors in the field of development also play a role in giving birth to the next generation biologically. As the nation's successor, young women are expected to be healthy so that the quality of the nation's children is physically, psychologically and intellectually healthy. Normally, young women experience menstruation every month with a span of 21-35 days each time they menstruate. The normal menstrual cycle physiologically describes the reproductive organs that tend to be healthy and not problematic. When young women are stressed, it can cause menstrual cycle disorders, This study aims to determine the relationship between stress levels and menstrual cycle disorders in adolescent girls in grades X and XI at the Nafsiah Stabat Health Vocational School in 2022. The type of research used is descriptive correlation with a cross sectional study design. The research was conducted at the Nafsiah Stabat Health Vocational School with a sample of 34 people. Based on the results of the chi-square test using a computer, the results (p value) = 0.000 which is smaller than 0.05 can be concluded that Ho is rejected and Ha is accepted at a 5% significance level. So there is a relationship between stress levels and menstrual cycle disorders in adolescent girls at the Nafsiah Stabat Health Vocational School in 2022 at the level of confidence/significant (a) = 5% (0.05) obtained p value = 0.